Effect of Adding Iron Tri ions (FeCl3) on Nutrient Consumption and Determining the causative factor for growth in the marine waters of the Syrian coast - عبد العزيز احمد; حازم كراوي; فيروز درويش (Latakia University Journal -Biological Sciences Series, 2022)
This research aims to study the effect of iron fertilization on phytoplankton growth and nutrient consumption in some areas of the Syrian coast. The experiment was conducted during the period from August 17 to September 6, 2019, and samples were collected from the mouth of the northern river al-Kabeer and the Higher Institute for Marine Research and transferred to the laboratories of the Higher Institute for Marine Research, where the water was enriched with iron and nutrients. Periodic samples were taken at 2-3 day intervals for nutrient and chlorophyll a measurements, the experiment spanned a period of 21 days. Iron played an important role in stimulating growth, as the results showed that the iron-fortified media recorded the highest values of phytoplankton growth and consumption of nutrient electrolytes compared to the rest of the preparations, The results showed that the concentration of iron 10 µmol / L is sufficient to reach the maximum growth of phytoplankton, as we did not notice clear differences in growth for the concentration of 100 µmol / L. Phytoplankton showed a clear growth ability in the two studied stations in the enrichment medium, where growth continued throughout the incubation period and a jump in growth occurred on the seventh day of the experiment and nutrients remained available in the medium until the end of the experiment, while the growth of phytoplankton was less in the control medium with a jump in Growth On the seventh day of the experiment, growth decreased on the twelfth day of incubation as a result of phosphate depletion from the medium. Iron played a role in the increased consumption of nutrients, especially silicates, as well as an increased reliance on ammonia as a source of nitrogen. The application and investment of the results of these experiments on various environmental fields and fish farms with economic and environmental returns is important.